2018
DOI: 10.1016/j.cancergen.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

H2AFY is a novel fusion partner of MECOM in acute myeloid leukemia

Abstract: The MECOM gene encoding a zinc finger protein that functions as a transcription factor, was located on chromosome 3q26, and rearrangements of MECOM often cause its overexpression in acute myeloid leukemia (AML). We identified H2AFY as a novel fusion gene partner of MECOM in an elderly male AML patient with cryptic 3q26 rearrangement using the whole transcriptome sequencing, who carried out abnormal karyotype of 46,XY,t(3;5)(q27;q31),add(14)(p11). We validated the existence of the unreported H2AFY-MECOM fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The encoded proteins fulfil a wide range of functions with signaling (7 genes), transcription (8 genes) and metabolism (10 genes) being the most prominent (Supplementary Table S9). Five of these genes have been studied in AML (see [16,18,19,20,21,22]).…”
Section: Resultsmentioning
confidence: 99%
“…The encoded proteins fulfil a wide range of functions with signaling (7 genes), transcription (8 genes) and metabolism (10 genes) being the most prominent (Supplementary Table S9). Five of these genes have been studied in AML (see [16,18,19,20,21,22]).…”
Section: Resultsmentioning
confidence: 99%
“…For example, H2AFY has a significant correlation with lipid metabolism-related HCC (40), as it can also alter the lipid metabolism of HCC cells and allow tumour cells to be more adaptable to the changing microenvironment (23). Some evidence indicates that H2AFY is a new fusion gene companion for MECOM gene in patients with AML and may promote the development of AML, but the exact mechanism is unclear (28). H2AFY has also been reported in melanoma, prostate cancer and colorectal cancer (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have shown that H2AFY is differentially expressed and plays corresponding biological functions in multiple tumour types, including HCC, lung cancer, prostate cancer, acute myeloid leukaemia (AML), melanoma, and colon cancer (15,(26)(27)(28)(29)(30). According to previously published studies, the role of H2AFY in tumours is very complex and it is very challenging to study H2AFY in tumours.…”
Section: Discussionmentioning
confidence: 99%
“…is a new fusion gene companion for MECOM gene in patients with AML and may promote the development of AML, but the exact mechanism is unclear (28). H2AFY has also been reported in melanoma, prostate cancer and colorectal cancer (26,29,30).…”
Section: Discussionmentioning
confidence: 99%